Manajemen Pembiayaan Bank Syariah: Sebuah Perkenalan - Achmad Lubabul Chadziq (JES (Jurnal Ekonomi Syariah), 2017)
The two main functions of banking are fund raising and channeling of funds. Distribution of funds in conventional banks with those contained in Islamic banks has an essential difference, both in terms of names, contracts, and transactions. In the conventional banking, channeling of this fund is known as credit while in sharia banking called as defrayal. Unlike the definition of credit that requires the debtor to repay the loan by giving interest to the bank, the defrayal based on sharia principles, the loan repayment with profit sharing is based on the agreement between the bank and the debtor. For example, defrayal with the principle of sale and purchase which is intended to buy goods, while those who use the principle of lease is intended to obtain services. The profit-sharing principle is used for cooperative efforts aimed at obtaining goods and services at once. Financing is a very important activity because with the financing, it will be obtained the main source of income and become a supporting case of the bank business continuity. Conversely, the management of bank which is not good will cause problems and cessation of business bank. Therefore, it is necessary to have a good sharia-financing management so that the distribution or financing to the customer can be effective and efficient in accordance with the objectives of the company and Islamic sharia itself. In this paper, author tries to explain how the concept of sharia financing management itself so that it is expected, both writer, colleague, student, and the public can better understand the management of Islamic finance. Keywords: Financing Management, Sharia Bank